2018
DOI: 10.1039/c8cp03320j
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study and computational modelling of cruzain cysteine protease inhibition by dipeptidyl nitriles

Abstract: Chagas disease affects millions of people in Latin America. This disease is caused by the protozoan parasite Trypanossoma cruzi. The cysteine protease cruzain is a key enzyme for the survival and propagation of this parasite lifecycle. Nitrile-based inhibitors are efficient inhibitors of cruzain that bind by forming a covalent bond with this enzyme. Here, three nitrile-based inhibitors dubbed Neq0409, Neq0410 and Neq0570 were synthesized, and the thermodynamic profile of the bimolecular interaction with cruzai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 42 publications
(55 reference statements)
1
44
0
1
Order By: Relevance
“…As shown in Figure a, the quantum mechanics (QM) region, described with the AM1d semiempirical Hamiltonian, contains the whole inhibitor, the residue Cys25, and the imidazole ring of His159 (His163 in the case of the cathepsin L cysteine protease). The AM1d Hamiltonian has previously been employed in different computational studies of the mechanisms of catalysis and the inhibition of cysteine proteases . The rest of the system, the protein and water molecules, were described with the OPLS‐AA and TIP3P force fields, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure a, the quantum mechanics (QM) region, described with the AM1d semiempirical Hamiltonian, contains the whole inhibitor, the residue Cys25, and the imidazole ring of His159 (His163 in the case of the cathepsin L cysteine protease). The AM1d Hamiltonian has previously been employed in different computational studies of the mechanisms of catalysis and the inhibition of cysteine proteases . The rest of the system, the protein and water molecules, were described with the OPLS‐AA and TIP3P force fields, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…On the basis of our results, we proposed that both irreversible inhibitors Cbz‐Tyr‐Ala‐CH 2 Cl and Cbz‐Phe‐Hph‐(S) are good candidates to develop an effective inhibitor of cruzain. Recently, Lameira and co‐workers studied the inhibition mechanism of cruzain by dipeptidyl nitriles using both isothermal titration calorimetry and the hybrid QM/MM approach . They concluded that the nucleophilic attack of Cys25 (cruzain numbering) and the proton transfer from His159 (cruzain numbering) take place in a single step and confirmed the reversible character of the inhibitor.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Aspects of both their covalent and non-covalent interactions must be considered, but how to do so remains an open question. We have recently shown [32] that careful QM/MM calculations on the covalent binding of dipepdidyl nitrile ligands to cruzain can correlate well with experimental binding data, but the procedure is not suitable for high throughput use where the interactions of multiple ligands with multiple enzymes requires to be evaluated. Recently, Waldner et al [33] have shown that, for a panel of serine proteases, substrate specificity that could not be understood from an analysis of static (crystal) structures, was interpretable once the differential dynamics of the proteins was considered.…”
Section: Introductionmentioning
confidence: 99%
“…As cisteíno proteases são enzimas com função proteolítica, ou seja, que realizam a hidrólise de peptídeos, promovida por três resíduos de aminoácidos presentes no sítio ativo (Figura 2) O mecanismo catalítico mais comum para as cisteíno proteases, mostrado no Esquema 1, é consistente com a presença de um par iônico, formado após a transferência de um íon H + do resíduo de cisteína para o de histidina, levando a enzima a possuir um sítio ativo ionizado em sua forma livre (CysS − /HisH + ). A existência do par iônico em cisteíno proteases, como a papaína e catepsinas, foi confirmada experimentalmente e por modelos computacionais (28,29), sendo uma das características que diferem cisteíno proteases de serino proteases, que dependem da interação com o substrato para a ativação do grupo que dará início à hidrólise (30). O par iônico no sítio ativo explica a maior reatividade das cisteíno proteases frente a espécies eletrofílicas, quando comparadas a outras espécies nucleofílicas contendo enxofre, especialmente em meios mais ácidos, uma vez que o ânion tiolato é cerca de 10 10 vezes mais nucleofílico que o grupo tiol neutro (24,25,31).…”
Section: Cruzaína a Principal Cisteíno Protease Do Trypanosoma Cruziunclassified